2019
DOI: 10.11114/jets.v6i12a.3931
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Reaction Time and 60 m Performance in Elite Athletes

Abstract: The aim of this study was to investigate the relationship between 60m sprint results and reaction times in athletes who took part in the World Indoor Athletics Championships. The reaction times and 60m sprint results were compiled for 483 sprinters (253 male, 230 female) who performed 60m sprint event. Corresponding data were obtained from archives of the official website of the International Association of Athletics Federation (IAAF). The relationship between reaction time and 60m sprint results were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
2
10
1
Order By: Relevance
“…Additionally, Hurdle clearance plays an imperative role for good performance (2) .The correlations between all variables were positive significant (p<0.01) difference each other. Compared to the previous study (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) ,correlations of the approach run phase, hurdle unit phase, run-in phase were greater in the present study.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Additionally, Hurdle clearance plays an imperative role for good performance (2) .The correlations between all variables were positive significant (p<0.01) difference each other. Compared to the previous study (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) ,correlations of the approach run phase, hurdle unit phase, run-in phase were greater in the present study.…”
Section: Discussioncontrasting
confidence: 91%
“…The results indicated that men had significant difference (p-value < 0.01) less time in Run-in than women. The results of current studies highly supported with previous https://www.indjst.org/ studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) .Hurdler clearance results revealed that women had Mean/SD (0.28±0.02) significant difference (p-value < 0.01) cross hurdle in less time than men (M/SD=0.35±0.03). Additionally, Hurdle clearance plays an imperative role for good performance (2) .The correlations between all variables were positive significant (p<0.01) difference each other.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When it comes to the 200m discipline, it is considered that certain biomechanical factors, the so-called propulsive impulse, which was confirmed by research [2] by examining the hypothesis of the most favorable reaction force on the substrate during the initial acceleration, and the way to achieve it. Another very important factor is the level of speed endurance of athletes, which is increasingly paid attention during the training process, running techniques, and arises as a product of certain anaerobic processes in the body and good neuromuscular coordination, which was present in shorter sections [10]. The best examples of speed endurance are the C. Lemmetre and U. Bolt sprinters.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the men's final 100m (London) and 200m (Moscow) and 100m (Moscow) and 400m (London) no statistical differences were achieved in the start reaction time. Gürses, & Kamiş [10] examine the relationship between the results of the 60-meter sprint and the reaction time of 483 athletes who participated in the World Indoor Athletics Championships. A positive moderate correlation was found between the mean values of all 60m sprint results and the start reaction time.…”
Section: Introductionmentioning
confidence: 99%